2008
DOI: 10.1152/physiolgenomics.00262.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromosome 17 on features of the metabolic syndrome in the Lyon hypertensive rat

Abstract: The metabolic syndrome (involving obesity, hypertension, dyslipidemia, insulin resistance, and a proinflammatory/prethrombotic state) is a major risk factor for cardiovascular disease. Its incidence continues to rise, in part because of the epidemic increase in obesity. The Lyon hypertensive (LH) rat is a model for hypertension and several other features of the metabolic syndrome, having high body weight, plasma cholesterol, and triglycerides, increased insulin-to-glucose ratio, and salt-sensitive hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Figure 1 shows, as previously described [25], that LH rats exhibit a much larger body weight than BN rats. Interestingly, LH-13 BN rats showed a significantly larger body weight than LH rats, while body weight was lower in BN-13 LH rats than in BN parents.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 1 shows, as previously described [25], that LH rats exhibit a much larger body weight than BN rats. Interestingly, LH-13 BN rats showed a significantly larger body weight than LH rats, while body weight was lower in BN-13 LH rats than in BN parents.…”
Section: Resultssupporting
confidence: 77%
“…Consequently, the parental strains were the same as in our previous study [25] and the framework of the protocol is identical for all the strains, as previously described, with the exception that some biochemical measurements differ among the different consomic strains, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…[112][113][114] Results of this approach make it clear that the SS phenotype of rats is determined by multiple different genes or by the combination of their effects into a polygenic form of inheritance. An additional contribution of this methodology has been the understanding that components of the SS phenotype (eg, insulin resistance 115 ) or the magnitude of its cardiac 98,116 and renal 99,[117][118][119] target organ damage may be determined by genetic influences distinct from those that control the hypertensive response to salt.…”
Section: Genetics and Ss Phenotype In Rodentsmentioning
confidence: 99%
“…8, 34 Therefore, we speculate there may be a gene or genes having pleiotropic effects on the MetS spectrum. In this study, we identified a cis -regulated gene on RNO17, RGD1562963 , as a putative driver gene regulating multiple downstream genes.…”
Section: Discussionmentioning
confidence: 96%